Non-English Department Students’ Perceptions of Using Chat GPT for English Texts Translation - Hertiki; Pimon, Parichat (Universitas PGRI Adi Buana Surabaya, 2026)
This study aims to examine non-English students' perceptions of utilizing ChatGPT for translating English texts. In the modern era, where individuals from all backgrounds converge to share knowledge, there is a growing necessity for precise translation of English texts. The formulation of the research question is as follows: What is the perception of non-English department students regarding ChatGPT as a tool for translating English text? This study employs descriptive qualitative methodology. Using ChatGPT for translation, seventh-semester non-English students at Universitas PGRI Adi Buana Surabaya were observed in order to collect the data. The interviews were conducted at Universitas PGRI Adi Buana Surabaya with five randomly chosen students, including 2 females and 3 males. The researcher conducted individual interviews with each of the five students, and the conversations were recorded as documentation of the research undertaken at the university. The data are then assessed thematically. The research findings indicate that the application of ChatGPT for translating English texts for non-English department students, from the students' viewpoint, presents a varied environment, encompassing: 1) User-Friendly and Accessible; 2) Speed versus Accuracy; 3) Striking a Balance Between User-Friendliness and Accuracy; 4) Adaptability in Translation Style Flexibility; and 5) Utilization Recommendations. This research provides significant insights for educators, educational technology developers, and others seeking to enhance digital tools such as ChatGPT.